Two Flavonoid Compounds as Antiproliferative Activity Against SP-C1 Cancer Tongue Cells from the Leaves of Rasamala (Altingia excelsa Nornha) - Risyandi Anwar; Arlette Setiawan; Supriatno Supriatno; Unang Supratman (Jurnal Kimia Valensi, 2018)
Two flavonoid compounds, kaempferol (1) and quercetin (2) have been isolated from the leaves of Rasamala (Altingia excelsa Nornha). The chemical structure of compounds 1 and 2 were identified by spectroscopic evidences including, UV, IR, 1D-NMR, 2D-NMR and MS as well as by comparing with previously reported spectral data.These compounds were isolated from this plant for the first time. Compounds 1 and 2 were evaluated for their antiproliferative activity against SP-C1 cancer tongue cells and showed IC50 values of 2.50 and 2.31 mM, respectively.